Personal style of the therapist. Therapist's expertise as a moderating variable? (Revista de Psicología, 2025)
Psychotherapy is a collaborative treatment based on the relationship between client and psychologist and although its effectiveness has been extensively demonstrated for a wide range of psychopathologies, there is still discussion about the guiding principles that lead to positive therapeutic outcomes. One of them is the personal style of the therapist and specifically the professional's expertise (measured in years of psychotherapeutic work). There is consensus that instructional flexibility is associated with the presence of therapeutic outcomes in general, but the extent to which professional expertise explains the variance of this factor and personal style functions in general is unknown. A socioprofessional questionnaire and the EPT-C were administered to a sample of 72 Argentine therapists matched on gender, age, theoretical framework and residence. The results highlight that more years of professional experience does not lead therapists to predominantly develop any particular function and that years of experience alone do not lead therapists to achieve greater instructional flexibility, which is one of the main promoters of the alliance and positive outcomes in multiple psychopathological conditions. Such results suggest: (a) the importance of adopting an active-constructive stance on the part of the therapist with respect to his or her own personal style and specific training in flexibility to adapt the therapeutic alliance and (b) that when considering the therapist as a general factor of change, the number of years of professional experience seems to be a necessary but not sufficient condition for obtaining positive therapeutic results.
Keywords: Personal style of the therapist; PST; clinical psychology; integration into psychotherapy; integrative cognitive behavioral psychotherapy